Modelling of the supersonic jet length for KT oxygen lance with 15 cm diameter and 1:1 ratio of O2: NG at electric arc furnace using computational fluid dynamics (CFD) - Mohd khairul, Ya'kub (2008)
A researched is conducted to study on optimization of supersonic jet lance at electric arc furnace for PERWAJA STEEL Kemaman, Terengganu. Due to the increasing of world steel demand, PERWAJA start to increase their steel production to grab the chance to increase their profit. However, there is one major problem for these companies; the current production cost of steel is too high due to increasing of energy and facilities in the world. Production of steel required a large amount of electrical energy usage. Thus, will increased the operation cost. Due to this problem, PERWAJA STEEL has doing cooperation with Universiti Malaysia Pahang to find the best solution. The most reliable way to solve the problem is by using modelling and simulation of KT oxygen lance using CFD softwre. This method is very efficient and cost saving compare to the expensive of experimental method. Optimization of oxygen lance will increased the chemical energy, reduce FeO that decreased the steelbar quality and this will decreased the electrical energy usage. Thus, the cost of production is decreased and the profit is increased.